Recent advances for SEI of hard carbon anode in sodium-ion batteries: A mini review - Meng, Jiaqi; Jia, Guofeng; Yang, Hongjun; Wang, Min (Frontiers in Chemistry, 2022)
The commercialization of sodium-ion batteries has been hampered by the anode's performance. Carbon-based anodes have always had great application prospects, but traditional graphite anodes have great application limitations due to the inability of reversible insertion/de-insertion of sodium ions in them, while hard carbon materials have the high theoretical capacity, low reaction potential has received extensive attention in recent years. Nevertheless, the low first cycle Coulomb efficiency and rapid capacity decline of hard carbon materials limited its application. SEI has always played a crucial role in the electrochemical process. By controlling the formation of SEI, researchers have increased the efficiency of sodium-ion battery anodes, although the composition of SEI and how it evolved are still unknown. This paper briefly summarizes the research progress of hard carbon anode surface SEI in sodium-ion batteries in recent years. From the perspectives of characterization methods, structural composition, and regulation strategies is reviewed, and the future development directions of these three directions are suggested. The reference opinions are provided for the reference researchers.